Comparison of surgical invasiveness between micro-endoscopic discectomy/microscopic discectomy and conventional hemilaminectomy in dogs - ITOH, Harumichi; NAKAICHI, Munekazu; ISERI, Toshie; NEMOTO, Yuki; ITAMOTO, Kazuhito; HORIKIRIZONO, Hiro; TANI, Kenji; SUNAHARA, Hiroshi (Journal of Veterinary Medical Science, 2023)
Micro-endoscopic discectomy (MED) or microscopic discectomy (MD) have been performed for disc herniation in humans. The purpose of this study was to compare the invasiveness of the hemilaminectomy in dogs between the approach using a cylindrical retractor for the MED/MD and a conventional open surgical approaches in dogs. First, as preliminary studies, we analyzed the suitability of the cylindrical retractor for the vertebral body of small to medium-sized dogs on the X-ray computed tomographic images using the three-dimensional analysis software, and confirmed that it was possible to open a bone window of an approximate length of 1.72 clto the spinal canal with the cylindrical retractor with a diameter 17 mm using two medium-sized canine cadavers. Next, to determine difference in the invasiveness of hemilaminectomy, the magnitude of tissue damage, surgical stress and postoperative pain were compared between the conventional open approach (hemilaminectomy group: HL group, n=6) and the surgical approach using the cylindrical retractor (MD group, n=6) in 12 beagle dogs. The plasma creatine phosphokinase, C-reactive protein and cortisol concentrations, incision length and University of Melbourne Pain Scale scores after the hemilaminectomy were significantly lower in the MD group than in the HL group. There were no significant differences between the durations of surgery and the other evaluated indices. The approach using the MD can provide a less invasive hemilaminectomy than the conventional approach in dogs.